Carvacrol Together with TRPC1 Elimination Improve Functional Recovery after Traumatic Brain Injury in Mice - Peters, Maximilian (Mary Ann Liebert, Inc., 2012)
Death of Central Nervous System (CNS) neurons following traumatic brain injury (TBI) is a complex process arising from a combination of factors, many of which are still unknown. It has been found that inhibition of transient receptor potential (TRP) channels constitutes an effective strategy for preventing death of CNS neurons following TBI. TRP channels are classified into seven related subfamilies, most of which are Ca(2+) permeable and involved in many cellular functions, including neuronal cell death. We hypothesized that TRP channels of the TRPC subfamily may be involved in post-TBI pathophysiology and that the compound 5-isopropyl-2-methylphenol (carvacrol), by inhibition of TRP channels, may exert neuroprotective effect after TBI. To test these suppositions, carvacrol was given to mice after TBI and its effect on their functional recovery was followed for several weeks. Our results show that neurological recovery after TBI was significantly enhanced by application of carvacrol. To better define the type of the specific channel involved, the effect of carvacrol on the extent and speed of recovery after TBI was compared among mice lacking TRPC1, TRPC3, or TRPC5, relative to wild type controls. We found that neurological recovery after TBI was significantly enhanced by combining carvacrol with TRPC1 elimination, but not by the absence of TRPC3 or TRPC5, showing a synergistic effect between carvacrol application and TRPC1 elimination. We conclude that TRPC1-sensitive mechanisms are involved in TBI pathology, and that inhibition of this channel by carvacrol enhances recovery and should be considered for further studies in animal models and humans.